2022
DOI: 10.1088/1361-6560/ac65d3
|View full text |Cite
|
Sign up to set email alerts
|

Roadmap: helium ion therapy

Abstract: Helium ion beam therapy for the treatment of cancer was one of several developed and studied particle modalities in the 1950’s, leading to clinical trials beginning in 1975 at the Lawrence Berkeley National Laboratory. The trial shutdown was followed by decades of research and clinical silence on the topic while proton and carbon ion therapy made debuts at research facilities and academic hospitals worldwide. The lack of progression in understanding of principle facets of helium ion beam therapy in terms of ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 218 publications
0
43
0
Order By: Relevance
“…For biological dose optimization, the modified microdosimetric kinetic model (mMKM) was used with the clinical parameters as described before [ 23 ]. All the dose specifications of helium ions are considered as biological doses (GyRBE).…”
Section: Methodsmentioning
confidence: 99%
“…For biological dose optimization, the modified microdosimetric kinetic model (mMKM) was used with the clinical parameters as described before [ 23 ]. All the dose specifications of helium ions are considered as biological doses (GyRBE).…”
Section: Methodsmentioning
confidence: 99%
“…5 Therefore, LET of the primary ion beam increases along the ion beam path and reaches its maximum at the end of the range. [6][7][8] Studies have reported LET dependence in EBT-2 and EBT-3 films, 9,10 but quantitative analyses of LET dependence in EBT-XD films are scarce. Therefore, the first aim of the current study was to characterize the proton LET dependence of EBT-XD films.…”
Section: Introductionmentioning
confidence: 99%
“…A recent roadmap discusses the potential role of helium ions in MIT. 53 Additional SHArc optimizations were attempted with various mixtures, for example, He+C; however, such mixtures did not provide ideal MIT conditions like improved D Phys and RBE homogeneity without increasing entrance channel dose contributions in the target volume and therefore,we conclude that this application of SHArc, that is, optimization with a single energy per angle to increase central target LET may not be feasible unless more beam energies are allowed during optimization. These results were anticipated considering prior multi-ion works,which showed difficulty in establishing uniform RBE/physical dose distributions while meeting primary optimization goals of target coverage homogeneity.…”
Section: Discussionmentioning
confidence: 93%